DESAFÍOS DE LA INVESTIGACIÓN EN SALUD EN AMÉRICA LATINA. DESAFÍOS DE LA INVESTIGACIÓN EN LAS FACULTADES DE ODONTOLOGÍA. - Lahoud Salem, Víctor (2003)
The scientific technological and the production of knowledge in a global world offer to the dental profession the opportunity to transform their practices clinic and to revolutionize the dentistry. Equally, the Declaration of Toronto about the Justness in Health (2002) it commits the professionals of the health and the international organizations to reaffirm and to promote among their members, the importance of the primary attention in health and the prevention and the commitment for revert all decision of the public sector and private that increases the inequities as regards health and to acclaim all decision guided to improve it, besides promoting the investigation on the problem of the bucal health.